PROGRAM APPLICATION FOR AUDIO AND VIDEO WITH PLAYS DELPHI 6 USING WINDOWS MEDIA PLAYER ACTIVEX CONTROLS - Tony Sugiarto; Ire Puspa W, Ir, MMSI Ire Puspa W, Ir, MMSI (Jurnal Sistem Informasi, 2005)
Along with the development of computer technology is so rapid, computers today arenot only used as a tool for the job but it can also be used as a medium ofentertainment, like listening to music or watching videos, so you no longer need thesemedia.In the play audio and video via computer media, there are two things to note is usedto build computer programs and software that have a facility combines elements ofaudio and video in one software. Software that can be used vary widely from thesimple to the complex which has a high level. Each level in the variation affects thelevel of satisfaction with the software user. Many of the actual products that can beselected to play audio and video, but distinguished between programming languageswith authoring software.